Theoretical-methodological process of formation of the institutional environment of environmental security of living population local level - Kirova, M. (Land Management, Cadastre and Land Monitoring, 2018)
Environmental problems of today present the danger of human existence at all levels - from local to global. The general state of ecological safety, both in Ukraine as a whole and in large cities, is rather complicated. There is a wide variety of factors (both natural and anthropogenic) that contribute to the further complication of its condition in the spatial-temporal aspect. This causes the urgent need for comprehensive study and solving of environmental safety issues.The purpose of the article is to study the evolution of the general concept of ecological safety, the theoretical and practical principles of environmental safety management, the definition of theoretical and methodological foundations of the process of formation of the institutional environment of ecological safety of the vital activity of the population at the local level.Environmental safety is considered by us as a dynamic component of the regional system, which ensures its harmonious development in the conditions of protection from real and potential human and natural influences. From the standpoint of a systematic approach to environmental safety management, we consider the region as a set of interconnected and mutually influential subsystems - natural and socio-economic.The most significant property that determines the specifics of environmental safety management is regionalization. It consists in identifying territories (regions) with a specific concentration and dominance of certain types and classes of danger within their borders.Institutionalisation involves the development of the ecological security system as a whole in the state and its separate territories, on the basis of a complex process of harmonization and implementation of environmental and economic imperatives, reflected in concepts, programs, laws and standards. Moreover, the imperative, as a set of requirements, defines the foundations of the functioning of institutions.The general problem of the development of the institutional environment of the environmental safety system is to eliminate contradictions that are characteristic of the process of implementing social, economic and environmental interests of economic entities, overcoming the general imperfection of the legislative framework regarding the system of application of market incentives that restrict and encourage economic activity in the desired direction.The institutional environment is considered as a basis for sustainable development as a whole and regulates the interaction of its three subsystems - economic (sustainable economic growth), environmental (equilibrium natural resource use) and social (social progress). It is the institutions with their ability to actively act on the micro, macro- and meso-levels of the economic system becoming one of the direct factors of economic evolution and security assurance.Actually, the process of ensuring environmental safety should include several key components, namely, the system of legal, institutional, organizational and financial means, which through integrated use, will contribute to the achievement of environmental policy objectives, increase its efficiency.Institutionalization is often understood as the process of streamlining and formalizing social relationships and relationships. In practice, this involves defining and consolidating socio-legal norms, rules, statuses and roles and bringing them into a system capable of satisfying socially important needs. In other words, in the case of the formation of an environmental safety system, it is a question of establishing a socio-ecological institute as a stable, normatively-secured form of social interaction between people.Thus, the process of institutionalization of environmental safety at the level of the territory of territorial communities must be carried out taking into account the theoretical basis of the system of nature management of financial and environmental security in the scenario logical and semantic model, which includes: institutionalization of the provision of functions with institutionalization of administration and incentive tools; institutionalization of the regulation function with the institutionalization of regulatory instruments; institutionalization of the functions of state control and monitoring with the institutionalization of the relevant instruments. In our opinion, the necessary prerequisites for institutional transformations are the completeness and consistency of the legislative framework, the separation of power, ownership and finance, increased public accountability, the formation of civil-law institutions and self-regulation organizations. The result of the research is the proposed logical-semantic model of the process of institutionalization of the system of environmental safety of life of the population at the local level.Keywords. Environmental safety, theoretical and methodological process, institutional environment, institutionalization, regional level, urban level